2021
DOI: 10.1101/2021.12.12.472274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NFE2L1-mediated proteasome function protects from ferroptosis

Abstract: ObjectiveFerroptosis continues to emerge as a novel modality of cell death with important therapeutic implications for a variety of diseases, most notably cancer and degenerative diseases. While susceptibility, initiation, and execution of ferroptosis have been linked to reprogramming of cellular lipid metabolism, imbalances in iron-redox homeostasis, and aberrant mitochondrial respiration, the detailed mechanisms of ferroptosis are still insufficiently well understood.Methods and ResultsHere we show that dimi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For example, it has been recently reported that the proteasome is affected by inducers in ferroptosis, which is mediated by the transcription factor nuclear factor erythroid-2, like-1 (NFE2L1). The ferroptosis inducers RSL3 and FIN56 increase the activity of NFE2L1, but erastin does not have this effect [27]. Moreover, inhibiting the function of GPX4 directly will not cause the wavelike transmission of death between cell populations, while inhibition of other key targets reportedly showed transmission [6].…”
Section: Important Regulatory Targets In Ferroptosis Metabolic Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been recently reported that the proteasome is affected by inducers in ferroptosis, which is mediated by the transcription factor nuclear factor erythroid-2, like-1 (NFE2L1). The ferroptosis inducers RSL3 and FIN56 increase the activity of NFE2L1, but erastin does not have this effect [27]. Moreover, inhibiting the function of GPX4 directly will not cause the wavelike transmission of death between cell populations, while inhibition of other key targets reportedly showed transmission [6].…”
Section: Important Regulatory Targets In Ferroptosis Metabolic Pathwaymentioning
confidence: 99%
“…Reduce iron level Ferritin Prominin2 [90] ALOX15 miR-522 [95] miR-129-5p RP11-89 [94] Reduce lipid peroxides ACC1 LKB1-AMPK axis [97] / iNOS [98] Effects on the GSH/GPX4 axis System Xc − DKK1, OTUB1 [102,105] Regulate the proteasomal activity / NFE2L1 [27] role in many disease models [85]. In ɑ-tocopherol (Vitamin E) and analogs of Fer-1, such as SRS15-72B, SRS15-72A, SRS16-80 and SRS16-86, have similar functions albeit different effects and stabilities [7,85,86].…”
Section: Acsl4mentioning
confidence: 99%
See 1 more Smart Citation
“…However, p53 can also inhibit ferroptosis by the inhibition of dipeptidyl peptidase 4 or through the enhancement of cyclin dependent kinase inhibitor 1 A (61). It has been reported that proteasome function is often inhibited during ferroptosis (62). Numerous metabolic and degradation pathways, including the ubiquitin-proteasome system, orchestrate the complex ferroptotic response through the regulation of iron accumulation or lipid peroxidation (63).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, oxidative stress is sensed and mitigated by GPX4 and its inactivation leads to lipid peroxidation and cell death in cells and mouse models (8). Interestingly, ferroptosis is linked to adaptive changes in protein homeostasis, as ferroptosis initiation is associated with diminished proteasomal activity and restoration of proteasomal activity protects cells from ferroptotic cell death (9). The ubiquitin-proteasome system (UPS) manages the degradation of unwanted, obsolete, or damaged proteins (10).…”
Section: Introductionmentioning
confidence: 99%